SF002-96-1, a new drimane sesquiterpene lactone from an Aspergillus species, inhibits survivin expression - Felix, Silke; Sandjo, Louis P.; Opatz, Till; Erkel, Gerhard (Beilstein Journal of Organic Chemistry, 2013)
Survivin, a member of the IAP (inhibitor of apoptosis) gene family, is overexpressed in virtually all human cancers and is functionally involved in the inhibition of apoptosis, regulation of cell proliferation, metastasis and resistance to therapy. Because of its upregulation in malignancy, survivin has currently attracting considerable interest as a new target for anticancer therapy. In a screening of approximately 200 strains of imperfect fungi for the production of inhibitors of survivin promoter activity, a new drimane sesquiterpene lactone, SF002-96-1, was isolated from fermentations of an Aspergillus species. The compound inhibited survivin promoter activity in transiently transfected Colo 320 cells in a dose dependent manner with IC50 values of 3.42 µM (1.3 µg/mL). Moreover, it also reduced mRNA levels and protein synthesis of survivin and triggered apoptosis.
Keywords: apoptosis; inhibitor; natural products; secondary metabolite; structure elucidation; survivin